2019
DOI: 10.1016/j.heliyon.2019.e02578
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ attitudes toward care of dying patients: A pre- and post-palliative course study

Abstract: BackgroundMany nursing students are not prepared to encounter death and care for patients who are at the end of life as newly educated nurses. The Frommelt Attitude Toward Care of Dying Scale (FATCOD) has been used to assess nursing students’ attitudes during their education and changes have been noted.ObjectiveTo examine nursing students’ attitudes towards care of dying patients before and after a course in palliative care.DesignA descriptive study with a pre and post design.Settings & participantsNursing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 26 publications
8
41
0
4
Order By: Relevance
“…Our study shows a statistically significant positive change in palliative care attitude after the course by 10.45 points. This result is in line with Berndtsson's finding that the mean score increased by 9.6 points after a dedicated five-week course, including 12 lectures [7]. Also, Henoch improved nursing students' attitudes by 6 points after five weeks of palliative care theoretical education [17].…”
Section: B Palliative Care Attitudesupporting
confidence: 88%
See 2 more Smart Citations
“…Our study shows a statistically significant positive change in palliative care attitude after the course by 10.45 points. This result is in line with Berndtsson's finding that the mean score increased by 9.6 points after a dedicated five-week course, including 12 lectures [7]. Also, Henoch improved nursing students' attitudes by 6 points after five weeks of palliative care theoretical education [17].…”
Section: B Palliative Care Attitudesupporting
confidence: 88%
“…Our course focused on nine of the AACN (2019) palliative care competencies and classified them into two aspects: 1) caring dying patients and their families (including competency 5,6,7,8,10,11,12), and 2) self-recognizing/self-coping (including competency 3, 15). Nursing students should be trained to have the competencies of assessing and treating physically, psychologically, socially, and spiritually with evidence-based pharmacologic and non-pharmacologic approaches (competency 7,10,11,12), through effective communication with the patients, patients' families, and the colleagues in the inter-professional team (competency 5, 6, 11), and by practicing ethical principles (competency 8). Nursing students also should be trained to identify their own ethical, cultural, and spiritual values and beliefs about death (competency 3) and implement the self-care strategies to cope with suffering, moral distress, and compassion fatigue (competency 15).…”
Section: B Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review and meta‐synthesis study by Wang 57 on nursing students’ experience of providing care for dying patients and their families reported that students had problems in managing the patients’ symptoms and ensuring their comfort. Berndtsson et al, 58 in their study, found that nursing students had difficulties in developing an appropriate care plan for the management of pain and other symptoms of dying patients. Accordingly, nursing students experience difficulties and need support in theoretical training and clinical practices in symptom management of palliative care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, palliative care education predominantly carried out by theoretical lectures which may be complained by both students and educators for lacking in practising. For example, Berndtsson used a didactic five-week palliative care course for the year three nursing students (Berndtsson, Margareta & Rejnö, 2019). Their study included 12 lectures: physical and psychological changes in the dying process, palliative diagnoses, terminal symptoms management, ethical issues, caring for families, and nurses' advocating roles in palliative care.…”
Section: Lecture-simulation-combine Education For Palliative Carementioning
confidence: 99%